Modelo matemático multivariado para análise de risco em sistemas dinâmicos - Chaves, Aline (2018)
The area of Dynamic Systems studies processes in which the evolution is established by a mathematical law, whose objective is to develop a mathematical theory of these processes that allows to understand and to predict its evolution. A complex structural system usually has a vast database containing random variables related to the system, which can provide invaluable information on the safety conditions of the structure. In this work, a mathematical model was developed, with the aid of the Multivariate Analysis and Structural Reliability techniques, which has the capacity to assist in the monitoring activity and in the prevention of anomalies in a highly instrumented concrete block, contributing to the accomplishment of actions before the occurrence of problems. The model was established with nine components, with each one representing an anomaly, and an alert system was implemented to represent the situation of the Dynamic System. A case study was carried out considering a highly instrumented concrete block of the Itaipu Hydroelectric Power Plant. The application of the model presented satisfactory results.